ANALISIS PENERAPAN KONSEP PDCA PADA PT MAYORA INDAH TBK DALAM MENINGKATKAN PENJUALAN DAN DAYA SAING DI INDUSTRI FMCG - Juliamida, Inka Sabila; Haludin, Guntur; Minarso, Mifthakul Fauzi; Natalia, Intan; Niser, Alifah; Iskandar, Syafna Hanifa (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Indonesia is experiencing rapid development, especially in the food and beverage sector. PT Mayora Indah Tbk, as one of the main players in this industry, continues to strive to improve its competitiveness. This study examines the implementation of PT Mayora Indah Tbk’s marketing strategy in the FMCG industry using a qualitative approach and case studies. The main focus of this study is the application of the Passion-Discipline-Creativity-Action (PDCA) method to improve sales performance and company competitiveness. The results of the study show that the application of PDCA, which includes passion, discipline, creativity, and action, has proven effective in responding to rapid market dynamics. In addition, product differentiation and continuous innovation are the main keys to maintaining Mayora as a market leader in the FMCG sector